Chronic kidney disease in an Aboriginal population: A nurse practitioner‐led approach to management. (December 2015) - Barrett, Elizabeth; Salem, Lesley; Wilson, Sue; O'Neill, Claire; Davis, Kathleen; Bagnulo, Sharif
Abstract: Problem: Chronic kidney disease (CKD) is a significant health problem impacting Australia's Aboriginal and Torres Strait Islander population. After age adjustment, the prevalence of kidney disease is 3.7 times higher in Aboriginal people and 7.3 times higher for end‐stage kidney disease compared with the wider population. Yet at an Aboriginal Community Controlled Health Service (ACCHS) with a significant patient population, fewer than expected numbers of Aboriginal patients were identified with CKD. Design: The ACCHS engaged a nurse practitioner to lead a systematic approach to the identification and treatment of CKD. Setting: This nurse practitioner‐led approach to CKD was developed and implemented at a rural NSW ACCHS, with the support of a partnership formed between the nurse practitioner, the ACCHS, a nephrologist from a referral hospital and a statewide NGO. Key measures for improvement: The primary measure for improvement has been to identify and stage patients with CKD and establish management plans as appropriate. Strategies for change: This nurse‐led project was established to: (i) identify patients with CKD; (ii) provide access for CKD patients to appropriate services; (iii) commence pharmacological and non‐pharmacological strategies that enable remission or regression of CKD; and (iv) educate practice GPs and other staff members on CKD clinical guidelines and best practice. Effects of change: The CKD project has improved access to essential health care for vulnerable and at‐risk populations, with 187 patients to date having been identified with kidney disease and staged for its severity. Lessons learnt: The need for strong multi‐disciplinary teamwork has been demonstrated with good communication strategies implemented.